Modelling injury-burden in rugby sevens - Fuller, C. W. (Journal of Science and Medicine in Sport, 2018)
Objectives: To develop a time-based model of injury-burden for international rugby sevens teams and to demonstrate its utility. Design: Descriptive, cohort study. Methods: Injury data recorded during seven seasons of the Sevens World Series were used to quantify the rate of injury and the rate at which injured players recovered from injury. An equation describing the rate at which injuries were sustained was combined with an equation for the rate at which injured players recovered from injury to produce a time-based equation for the injury-burden of rugby sevens players at any point in time during a season. Results: The overall rates at which match and training injuries were sustained (incidence of injury) were 108.6 (95% confidence interval: 101.6-116.1) injuries/1000 player-match-hours and 0.91 (95% CI: 0.65-1.27) injuries/1000 player-training-hours, respectively. Injured players recovered from injury according to a first-order rate equation with a rate constant of 0.0257 days-1 calculated from the median severity of injuries sustained (27 days). The time-based injury-burden values predicted from the proposed kinetic model of injury-burden closely matched the values recorded in the Sevens World Series. Conclusions: For governing bodies in rugby, the proposed model provides a way to examine the consequences of changes in the number and timing of international rugby sevens tournaments. For individual teams, the model provides a means to forecast and manage the team`s injury-burden as a function of the team`s scheduled match and training loads throughout a season.